Performance during consecutive days of laboratory time-trials in young and veteran cyclists - Fell, J.; Haseler, L.; Gaffney, P.; Reaburn, P.; Harrison, G. (The Journal of Sports Medicine and Physical Fitness, 2006)
Aim: There is a common belief amongst athletes and coaches that older athletes need longer recovery time between training sessions and following competition. This study was undertaken to investigate the influence of age on recovery from high intensity endurance exercise in well-trained cyclists. Methods: Nine young and 9 veteran cyclists (mean±SD: young 24±5 years, veteran 45±6 years) performed 3 consecutive days (T1-T3) of laboratory based cycling time trials of 30-min duration (TT30). Mean power output, heart rate (HR), and blood lactate were measured throughout each TT30. Non-specific performance tests of fatigue were undertaken before and after the TT30 on each test day. Non-specific tests included, a maximal voluntary isometric contraction of the quadriceps muscle (MVIF), a countermovement jump (CMJ), a 10-s cycle sprint (10ST), and serum creatine kinase activity (CK). Results: Statistical analysis revealed that there were no significant group differences between young and veteran subjects for initial fitness or training status. Over T1-T3 both groups maintained average power during the TT30 (young and veteran results combined; 3.49±0.38, 3.5±0.36 and 3.52±0.35 W.kg-1, T1-T3, respectively). For both groups serum CK activity was significantly elevated at T2 and T3, and mean HR during the TT30 was significantly lower at T3 (~3 b.min-1). There were no group differences or significant within group interactions across the 3 days for MVIF or 10ST but there was a significantly lower CMJ height by T3 in both young and veteran (~3%). MVIF was significantly lower after TT30 each day but had fully recovered by the following day. Conclusions: These findings suggest that high-intensity endu-rance performance is maintained in both well-trained young and veteran cyclists following 3 consecutive days of maximal 30-min laboratory time trials.